Perlindungan Hukum Terhadap Keluarga Tersangka Tindak Pidana Korupsi Dari Dampak Perampasan Aset Ditinjau Berdasarkan Kajian Pasal 34 UUD 1945 - Murry Mirranda; Aarce Tehupeiory (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
In Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, Corruption can be categorized into seven types, namely 1) state financial losses; 2) bribery; 3) extortion; 4) embezzlement in office; 5) fraud; 6) conflict of interest in the procurement of goods and services; and 7) gratification. The construction of the criminal law system, especially regarding corruption, which has been developed recently in Indonesia still aims to uncover crimes that have occurred, find the perpetrators and punish the perpetrators of criminal acts with criminal sanctions, especially